Performance enhancement of residential air conditioning system using fal2o3 and tio2-polyolester nanolubricant - Agus, Nugroho (2023)
Residential Air Conditioning (RAC) system plays important role for everyone’s comfort at home and office. This research is determined by a motivation to reduce the global warming effect caused by the RAC system and increase the coefficient of performance (COP) and energy saving. This study proposes the replacement of polyolester (POE) as a conventional lubricant using FAl2O3-POE and TiO2-POE nanolubricants for better performance and efficiency and then replacing the existing refrigerant R410a using R32, which has a lower Global Warming Potential (GWP). The objectives of this study are (i) to characterize the FAl2O3-POE and TiO2-POE nanolubricant thermophysical properties for application in the RAC system working with refrigerant R410a dan R32, and (ii) to evaluate the FAl2O3-POE and TiO2-POE nanolubricant performance in the RAC system working with refrigerant R410a dan R32, and (iii) to optimize the working operation of the FAl2O3-POE and TiO2-POE nanolubricant for RAC system using Response Surface Method (RSM). A two-step method was adopted to formulate FAl2O3-POE and TiO2-POE nanolubricant. The stability of nanolubricants was determined at three levels: visual, UV visible spectrophotometry, and zeta potential. In FAl2O3 and TiO2-based nanolubricants, characterization of dynamic viscosity with RheolabQC showed a maximum increase of 11.36% and 16.70%, respectively. In comparison, a report on thermal conductivity test with c-Therm showed a full augmentation of 4.35% and 3.44%. And then, tribology test results suggest a maximum COF reduction of 35.8% and 27.144% in FAl2O3-POE and TiO2-POE nanolubricants, respectively. The highest increase in COP in the FAl2O3-POE/R410a and FAl2O3-POE/R32 systems are 24.59% at 0.15 vol% with 0.442 kg and 32.26% at 0.15 vol% with 0.442 kg of initial refrigerant charge, respectively. And then, the highest increase in COP in the TiO2-POE/R410a and TiO2-POE/R32 system is 14.75% and 22.58% at 0.11 vol% with 0.442 kg of initial refrigerant charge, respectively. The vibration findings show that using both types of nanolubricant in the range of 0.02-0.15 vol% is allowable for long-term use. The desirability function Central Composite Design RSM suggests the optimum operating conditions for all types of nanolubricants with R410a and R32 are at a concentration of 0.11 vol% with an initial refrigerant charge of 0.442 kg. The standard error of optimization is within 0.012%-0.024%.